Transcriptional response to mild therapeutic hypothermia in noise-induced cochlear injury - Rincon Sabatino, Samantha; Sangaletti, Rachele; Griswold, Anthony; Dietrich, W. Dalton; King, Curtis S.; Rajguru, Suhrud M. (Frontiers in Neuroscience, 2024)
Prevention or treatment for acoustic injury has been met with many translational challenges, resulting in the absence of FDA-approved interventions. Localized hypothermia following noise exposure mitigates acute cochlear injury and may serve as a potential avenue for therapeutic approaches. However, the mechanisms by which hypothermia results in therapeutic improvements are poorly understood. Here we perform transcriptomic analysis of cochleae from juvenile rats that experienced noise-induced hearing loss (NIHL) followed by hypothermia or control normothermia-treatment. Differential gene expression results from RNA-sequencing at 24 hours post-exposure to noise suggest that NIHL alone results in increased inflammatory and immune defense responses, involving complement activation and cytokine-mediated signaling. Hypothermia treatment post-noise, in turn, may mitigate the acute inflammatory response. This study provides a framework for future research to optimize hypothermic intervention for ameliorating hearing loss and suggests additional pathways that could be targeted for NIHL therapeutic intervention.